Multi-Level QR-MLQR Code for Secure Message Distribution or Multi-Type File Sharing - Sravya Gattupalle, Bannur.Dilip Kumar Reddy (International Journal of Advanced Science and Technology, 2020)
The Quick Response (QR) code is used for providing security to information and quick perusing applications. The proposed multi-level QR code verification method is utilized to check unique substance in generated QR code. The QR code was intended for capacity data and high speeds perusing application . In this paper a multi-level QR code that has multiple levels is proposed that is used to archive confirmation. The multi-level QR code which implies 3 levels, private level ,public level and perceptive level. The public level is same as the standard QR code model and it is discernable by any established QR code applications . The private level permits us not exclusively to construct the capability limit of QR code that can recognize duplicates. The perceptive level is used for validating the other two layers. The results comes about demonstrating an ideal reclamation of private data or a document shared among two sources. It additionally features the likelihood of utilizing multi-level QR code for message validation or for sharing a document of any type.